2019
DOI: 10.1016/j.jvn.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled feasibility trial of a home-based walking behavior–change intervention for people with intermittent claudication

Abstract: L. M. (2019). A randomized controlled feasibility trial of a home-based walking behavior-change intervention for people with intermittent claudication. JOURNAL OF VASCULAR NURSING, 37(2), 135-143. https://doi. ABSTRACTWalking treatment is recommended for improving intermittent claudication (IC), a debilitating symptom of leg pain caused by peripheral arterial disease. However, centre-based exercise programmes offered in a community or hospital setting are often not implemented or adhered to. We developed a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Furthermore, this study also included a feasibility evaluation of the different assessments. Our findings were in line with earlier publications, that is, 2 recent studies also reported difficulties (55% and 50% baseline and follow-up data, respectively [ 43 , 45 ]) in collecting physical activity data using a triaxial pedometer or accelerometer on the hip. A possible explanation for these missing values might be the instruction to wear the monitor during waking hours compared with a more compliant 24-hour protocol [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, this study also included a feasibility evaluation of the different assessments. Our findings were in line with earlier publications, that is, 2 recent studies also reported difficulties (55% and 50% baseline and follow-up data, respectively [ 43 , 45 ]) in collecting physical activity data using a triaxial pedometer or accelerometer on the hip. A possible explanation for these missing values might be the instruction to wear the monitor during waking hours compared with a more compliant 24-hour protocol [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the short intervention duration, a clinically relevant improvement was found in the WIQ distance score [ 41 ]. As this study was designed to primarily evaluate patients’ satisfaction and acceptance, our results complement contemporary pilot studies in the field of eHealth solutions in patients with IC [ 20 , 42 - 45 ] .…”
Section: Discussionmentioning
confidence: 77%
“…Of the included trials, three were non-randomised and compared HEPs with SEPs . The 28,30,36,38,[41][42][43]45,47 remaining trials were RCT's, with nine comparing HEPs with SEPs , three comparing HEPs with basic exercise advice 31,32,48 , two comparing HEPs with both these groups 18,46 and six comparing HEPs to no exercise controls 17,19,29,39,49,50 .…”
Section: -35mentioning
confidence: 99%
“…MOSAIC was systematically developed to target the salient factors identified from these two models12 23 and includes behavioural change techniques to facilitate the uptake and maintenance of walking exercise 24. This protocol was informed by a preliminary study which demonstrated that the MOSAIC intervention and trial procedures were acceptable to participants and clinicians and feasible to deliver 26…”
Section: Introductionmentioning
confidence: 99%
“…Crucial conditions to support health behavioural change, such as increasing self-directed walking exercise, are an individual’s capability (eg, knowledge and understanding that walking exercise is a treatment for intermittent claudication), opportunity (eg, identifying an appropriate environment place to walk) and motivation (eg, attitudes and beliefs about walking as a treatment) 21–23. Evidence suggests that targeting these factors using behavioural change techniques (eg, setting walking goals, action planning22 24 or motivational interviewing25) in addition to exercise or advice may increase walking ability in people with intermittent claudication 24 26…”
Section: Introductionmentioning
confidence: 99%